Congestion control algorithm based on jitter detection in metro Ethernet networks - HAO Jun-rui1; YU Shao-hua1 (Tongxin xuebao)
A novel congestion control algorithm （JDCC） for multimedia traffics was proposed. JDCC improves the QoS of multimedia stream in metro Ethernet network by detecting and discarding packets that accumulated enough jitter so as to maintain a high bandwidth for packets that stay within the multimedia stream’s jitter tolerance. Simulation results have shown that the proposed scheme can effectively lower the average received packet jitter than that using traditional congestion control algorithm RED and DropTail. Moreover, the proposed scheme can improve the useful goodput of the received packets when compared to RED and DropTail.